Composição e variabilidade espaço-temporal da meiofauna de uma praia arenosa na região amazônica (Ajuruteua, Pará) - GOMES, Tatianne Pereira (2013)
The present study investigates the spatio-temporal changes in the meiofauna community along the intertidal zone of Ajuruteua Beach, State of Pará, Brazil. Samples were collected during spring tides at different levels of the beach face every two months from April 2003 to February 2004. The material was sampled using a cylindrical corer (3.14 cm2) and fixed with 5% saline formalin. In the laboratory, samples were sieved through a 0.063 mm mesh screen and the retained organisms were identified at higher taxonomic levels, counted and preserved in ethanol 70%. Meiofauna was composed of eight groups: Turbellaria, Nematoda, Tardigrada, Polychaeta, Oligochaeta, Acari, Copepoda and nauplius (Copepoda). Nematoda was the dominant group, representing 74% of total organisms, followed by Copepoda (19%). A clear faunal zonation was observed on three lines parallel to the shoreline, which showed significant differences in abundance, richness and density of the main taxonomic groups. The mean density was lowest in April and highest in December. The highest densities and richness were recorded in the mid intertidal zone, while the lowest values were recorded in the upper and lower intertidal zones. Meiofauna community was most rich and abundant during the dry months, although differences were not significant between climatic periods. The main factors